Back Cover: Experimentally Calibrated Analysis of the Electronic Structure of CuO+: Implications for Reactivity (Angew. Chem. Int. Ed. 52/2018). Issue 52 (4th December 2018) - Srnec, Martin; Navrátil, Rafael; Andris, Erik; Jašík, Juraj; Roithová, Jana
Abstract : The presence of a [CuO] + unit has often been used to explain the unique oxidation reactivity of copper‐containing enzymes. In their Communication on page 17053 ff., M. Srnec, J. Roithová, and co‐workers use cryogenic spectroscopy of gaseous ligated CuO + to acquire the first high‐resolution spectroscopic data for these complexes, which sheds light on the copper–oxygen bonding.